Historical references of natural and traditional medicine for training the internal medicine resident - Maricel Hechavarria Torres; María Eugenia García Céspedes; María Asunción Tosar Pérez (Centro Provincial de Información de Ciencias Médicas, 2021)
During the last decade, diverse countries among them Cuba, are reviewing  approaches and methodologies being used to train the specialist doctors.  On this regard, historical and logical references which give bases to the natural and traditional medicine are evaluated in this work, for the professional skills of the internal medicine resident.  Likewise, the different stages through which the natural and traditional therapies have developed in Cuba, and how this therapeutic group have been strengthen from the theoretical and practical point of view are described.